Physical characterization of single convergent beam device for teletherapy: Theoretical and Monte Carlo approach - Figueroa, Rodolfo G. (2015)
The main purpose of this work is to determine the feasibility and physical characteristics of a new teletherapy device of radiation therapy based on the application of a convergent x-ray beam of energies like those used in radiotherapy providing highly concentrated dose delivery to the target. We have denominated it Convergent Beam Radio Therapy (CBRT). Analytical methods are developed first in order to determine the dosimetry characteristic of an ideal convergent photon beam in a hypothetical water phantom. Then, using the PENELOPE Monte Carlo code, a similar convergent beam that is applied to the water phantom is compared with that of the analytical method. The CBRT device (Converay®) is designed to adapt to the head of LINACs. The converging beam photon effect is achieved thanks to the perpendicular impact of LINAC electrons on a large thin spherical cap target where Bremsstrahlung is generated (high-energy x-rays). This way, the electrons impact upon various points of the cap (CBRT condition), aimed at the focal point. With the X radiation (Bremsstrahlung) directed forward, a system of movable collimators emits many beams from the output that make a virtually definitive convergent beam. Other Monte Carlo simulations are performed using realistic conditions. The simulations are performed for a thin target in the shape of a large, thin, spherical cap, with an r radius of around 10-30 cm and a curvature radius of approximately 70 to 100 cm, and a cubed water phantom centered in the focal point of the cap. All the interaction mechanisms of the Bremsstrahlung radiation with the phantom are taken into consideration for different energies and cap thicknesses. Also, the magnitudes of the electric and/or magnetic fields, which are necessary to divert clinical-use electron beams (0.1 to 20 MeV), are determined using electromagnetism equations with relativistic corrections. This way the above-mentioned beam is manipulated and guided for its perpendicular impact upon the spherical cap. The first results that were achieved show in-depth dose peaks, having shapes qualitatively similar to those from hadrontherapy techniques. The obtained results demonstrate that in-depth dose peaks are generated at the focus point or isocenter. These results are consistent with those obtained with Monte Carlo codes. The peak-focus is independent of the energy of the photon beam, though its intensity is not. The realistic results achieved with the Monte Carlo code show that the Bremsstrahlung generated on the thin cap is mainly directed towards the focus point. The aperture angle at each impact point depends primarily on the energy beam, the atomic number Z and the thickness of the target. There is also a poly-collimator coaxial to the cap or ring with many holes, permitting a clean convergent-exit x-ray beam with a dose distribution that is similar to the ideal case. The electric and magnetic fields needed to control the deflection of the electron beams in the CBRT geometry are highly feasible using specially designed electric and/or magnetic devices that, respectively, have voltage and current values that are technically achievable. However, it was found that magnetic devices represent a more suitable option for electron beam control, especially at high energies. The main conclusion is that the development of such a device is feasible. Due to its features, this technology might be considered a powerful new tool for external radiotherapy with photons.